IMPLEMENTASI KONSEP “ZERO WASTE PRODUCTION MANAGEMENT” BIDANG PERTANIAN: PENGOMPOSAN JERAMI PADI ORGANIK DAN PEMANFAATANNYA - Yuwono, Arief Sabdo (Bumi Lestari, 2013)
Abstract The huge amount of rice straw as by-product of rice production system and the potential use of it as raw material of compost production for organic rice cultivation was the background of this research. Here, rice straw was concerned as raw material to produce compost instead of as waste from rice cultivation. The objectives of the research were to implement the concept of “Zero waste production management” in agriculture by composting rice straw generated from an experimental field; to develop an input-output (waste-compost) mass balance in organic rice cultivation system; and, to apply the resulted compost on the rice field. Materials necessary for the research covered an experimental organic rice field located in Bogor Municipality, rice seed, rice straw and goat manure. The rice field obtained organic fertilizer merely from compost without any synthetic fertilizer. The produced rice straw and goat manure were composted by natural static pile method. The result of the research indicated that waste-compost mass balance based on one hectare rice field showed that the produced straw was ± 14.1 ton and the resulted compost was around 11.3 ton. It is merely 7 ton from the produced compost necessary to apply in one hectare of rice field according to The Ministry of Agriculture recommendation. It can be concluded that if the entire rice straw produced from one hectare of rice field was composted, then the rice field could be compost self sufficient and even the rest of 4.3 ton could be utilized for other purposes.
Keywords: Keywords: compost, organic rice, rice straw, zero waste production management